2002
DOI: 10.1038/sj.onc.1205542
|View full text |Cite
|
Sign up to set email alerts
|

CL100 expression is down-regulated in advanced epithelial ovarian cancer and its re-expression decreases its malignant potential

Abstract: Although early stage ovarian cancer can be e ectively treated with surgery and chemotherapy, the majority of cases present with advanced disease, which remains essentially incurable. Unfortunately, little is known about the genes important for the development and progression of this disease. In this study, the expression of 68 phosphatases was determined in immortalized ovarian epithelial cells (IOSE) and compared to ovarian cancer cell lines. CL100, a dual speci®city phosphatase, displayed 10 ± 25-fold higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
4
39
2
Order By: Relevance
“…[19][20][21] Also, nuclear localization of DUSP1 has been reported in ovarian cancer as well as in fibroblasts, 22,23 whereas we did not detect any strong nuclear staining. All prostate carcinomas exhibited decreased expression compared to BPH, the basal cells of normal prostate or PIN, and in most of the cases, there was complete or almost complete lack of staining.…”
contrasting
confidence: 45%
See 2 more Smart Citations
“…[19][20][21] Also, nuclear localization of DUSP1 has been reported in ovarian cancer as well as in fibroblasts, 22,23 whereas we did not detect any strong nuclear staining. All prostate carcinomas exhibited decreased expression compared to BPH, the basal cells of normal prostate or PIN, and in most of the cases, there was complete or almost complete lack of staining.…”
contrasting
confidence: 45%
“…In ovarian cancer cells, the reexpression decreased the malignant potential of the cells by inhibiting anchorage-dependent and -independent cell growth as well as cell motility. 22 Whereas, in pancreatic cancer cells, the downregulation decreased cell proliferation and tumorigenicity in nude mouse tumor model.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…(24,35,36). More recently, decreased expression of MKP-1 has been strongly associated with the advanced progression of human ovarian cancers (37). Yet, the regulatory mechanisms underlying sustained ERK1/2 activation and MKP-1 downregulation have not been well characterized.…”
Section: Exogenous Mkp-1 Phosphatase Activity Decreases Erk Phosphorymentioning
confidence: 99%
“…The level of DUSP1 was also investigated in human tumors. These initial studies revealed a higher DUSP1 expression in a range of human epithelial tumors including prostate, colon, and bladder, however, the expression of DUSP1 in tumors decreased progressively with a higher histological grade [15][16][17].Some studies also suggested that DUSP1 was involved in tumor therapy efficiency [18][19][20][21][22]. The function and mechanism of DUSP1 in tumors may be varied and complex.…”
Section: Introductionmentioning
confidence: 99%